Implementation of the Principal’s Visionary Leadership in Improving the Quality of Education at SMA Negeri 1 Sukadana - Cholik, Muhammad; Syahrudin, Husni; Sanulita, Henny; Imran, Imran; Waruwu, Marinu (FKIP - Universitas Riau, 2025)
This study is grounded in the importance of visionary leadership in improving the quality of education at SMA Negeri 1 Sukadana. Visionary leadership is considered essential for guiding the entire school community toward shared goals through a clear vision, effective empowerment, and continuous evaluation. This research aims to describe how the principal formulates the school’s vision and mission, empowers teachers and staff, builds work motivation, and implements ongoing evaluations to enhance educational quality. A qualitative approach with a case study design was employed, utilizing in-depth interviews, participatory observations, and document analysis. The findings indicate that the school’s vision and mission were collaboratively developed and disseminated through various formal and informal forums. Teacher and staff empowerment was carried out through training, structured task distribution, and active involvement in decision-making processes. Work motivation was fostered through appreciation and warm interpersonal communication, while quality evaluation was conducted regularly and followed by program improvements. In conclusion, the principal’s visionary leadership plays a significant role in creating a collaborative work culture and supporting the continuous improvement of educational quality.